Analysis of Mathematic Literation Ability Through A Relaistic Approach to Students VII Ms Thalia Home Schooling - Thalia Avelina; Wahidin Wahidin (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2021)
This research is a case study which aims to determine the feasibility of learning mathematics with a realistic approach to knowing mathematical literacy skills and knowing the types of errors made by grade VII students of SMP MS. Thalia Home Schooling 2020/2021 school year. This type of research used by researchers in qualitative research methods is a type of case study research (Case Study). The subjects of this study were 4 junior high school students. The data collection instruments were observation sheets, test questions, teacher and student interview sheets. The results of this study indicate that learning mathematics at Ms. Thalia Home Schooling students of class VII of the 2020/2021 academic year have not met the characteristics of the relalistic approach. Most students' mathematical literacy abilities are at level 1 and level 6 with the percentage of student achievement of 100% and 75%. As well as student errors are more dominant because of errors in language interpretation with the percentage of students who make mistakes is 75%.